2006
DOI: 10.1002/icd.462
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relation between memory, gestural communication, and the emergence of language in infancy: a longitudinal study

Abstract: The relationship between recall memory, visual recognition memory, social communication, and the emergence of language skills was measured in a longitudinal study. Thirty typically developing Swedish children were tested at 6, 9 and 14 months. The result showed that, in combination, visual recognition memory at 6 months, deferred imitation at 9 months and turn-taking skills at 14 months could explain 41% of the variance in the infants' production of communicative gestures as measured by a Swedish variant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 52 publications
(70 reference statements)
2
41
0
1
Order By: Relevance
“…In a previous study, Heimann et al (2006) documented a relationship between recall memory at 9 months (deferred imitation), communication skills at 14 months (joint attention (JA)), and gestural communication at 14 months. The current study investigates whether a similar relationship exists between these infant skills and linguistic/cognitive performance measured long after the infancy period-at 4 years of age.…”
Section: Recall Memory; Deferred Imitation; Joint Attention; Pre-verbmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous study, Heimann et al (2006) documented a relationship between recall memory at 9 months (deferred imitation), communication skills at 14 months (joint attention (JA)), and gestural communication at 14 months. The current study investigates whether a similar relationship exists between these infant skills and linguistic/cognitive performance measured long after the infancy period-at 4 years of age.…”
Section: Recall Memory; Deferred Imitation; Joint Attention; Pre-verbmentioning
confidence: 96%
“…Recently, Heimann et al (2006) reported a short-term longitudinal study showing that deferred imitation and joint attention both influence the development of language and communication skills in infancy. Deferred imitation at 9 months was the single strongest predictor of nonverbal communication at 14 months, but the predictive power increased substantially when deferred imitation and joint attention were used in combination.…”
mentioning
confidence: 99%
“…Studies have found considerable variation in children's rates of elicited imitation during experimental tasks (e.g., Heimann, Strid, Smith, Tjus, Ulvund, & Meltzoff, 2006) as well as in their rates of spontaneous imitation, or "matching behavior" (Uzgiris, Benson, & Vasek, 1983, p. 1), occurring during natural dyadic interactions without direct elicitation (Hwang, & Windsor, 1999;Masur & Rodemaker, 1999;Snow, 1989). Such individual differences in vocal/verbal imitation rate are also associated with consequences for vocabulary acquisition, a critical measure of language development and a predictor of early literacy (Bornstein, Tamis-LeMonda, & Haynes, 1999).…”
Section: Abstract Imitation; Mother-infant Interaction; Vocabulary; Rmentioning
confidence: 99%
“…For example, infants' gaze following behavior at 10 to 11 months of age significantly predicts accelerated vocabulary growth through to 2 years of age (Brooks and Meltzoff 2008). In addition, Heimann et al (2006) showed that in typically developing children, visual recognition memory, deferred imitation, and turn taking skills predicted communicative gestures, while deferred imitation at 14 months also predicted vocal comprehension.…”
Section: Discussionmentioning
confidence: 98%